MENUMBUHKAN KARAKTER GEMAR MEMBACA MELALUI STRATEGI SAMISATE DAN SABUSOTO - Yeti Supriati (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2022)
Abstract The distance between teachers and students during distance learning during the current Covid-19 pandemic makes it increasingly difficult to cultivate character. Teachers must have tips and tricks to insert efforts to cultivate student character on the sidelines of learning. This study aims to comprehensively describe the cultivation of a character who likes to read during distance/online learning that the author uses the SAMISATE (One Week One Theme) and SABUSOTO (One Month One Character) method. This study uses a descriptive qualitative research design with data collection techniques from 124 students, covering students' responses to reading assignments and their learning outcomes in Indonesian subjects for two semesters. The results showed that the SAMISATE and SABUSOTO methods had an impact on increasing students' active participation in reading activities as evidenced by the increasing number of students who submitted reports on their reading results to the teacher, reaching 95% of the total number of students. In addition, it also has an impact on increasing Indonesian language learning outcomes in semester tests which reach an average of 90 compared to the previous semester's score of 83. This is because the increase in reading habits has an impact on increasing students' literacy competence which is closely related to the ability to understand exam question. The research findings indicate that the SAMISATE and SABUSOTO methods can be used to instill the character of reading fondness in students.   Abstrak Berjaraknya antara guru dan siswa ketika pembelajaran jarak jauh di masa pandemi Covid-19 sekarang ini membuat semakin sulitnya penanaman karakter. Guru harus memiliki tips dan trik untuk menyisipkan upaya penanaman karakter siswa di sela-sela pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan secara komprehensif mengenai penanaman karakter gemar membaca saat pembelajaran jarak jauhdaring yang penulis lakukan dengan menggunakan strategi SAMISATE (Satu Minggu Satu Tema) dan SABUSOTO (Satu Bulan Satu Orang Tokoh). Penelitian ini menggunakan desain penelitian kualitatif deskriptif dengan teknik pengumpulan data dari 124 siswa, meliputi respon siswa terhadap tugas membaca dan hasil belajar mereka dalam mata pelajaran Bahasa Indonesia selama satu semester. Hasil penelitian menunjukkan bahwa strategi ini berdampak pada meningkatnya partisipasi aktif siswa dalam kegiatan membaca. Selain itu juga berdampak pada peningkatan hasil belajar Bahasa Indonesia pada ulangan harian dan ulangan semester. Kompetensi siswa dalam menulis pun meningkat. Temuan penelitian mengindikasikan strategi SAMISATE dan SABUSOTO  dapat digunakan untuk menanamkan karakter gemar membaca pada siswa.